Perceptual distances of breathy voice quality: A comparison of psychophysical methods - Patel, Sona (2009)
OBJECTIVE: Experiments to study voice quality have typically used rating scales or direct magnitude estimation to obtain listener judgments. Unfortunately, the data obtained using these tasks is context-dependent, which makes it difficult to compare perceptual judgments of voice quality across experiments. The present experiment describes a simple matching task to quantify voice quality. The data obtained through this task was compared to perceptual judgments obtained using rating scale and direct magnitude estimation tasks to evaluate whether the three tasks provide equivalent perceptual distances across stimuli. METHODS: Ten synthetic vowel continua that varied in terms of their aspiration noise were evaluated for breathiness using each of the three tasks. Linear and nonlinear regression was used to compare the perceptual distances between stimuli obtained through each technique. RESULTS: Results show that the perceptual distances estimated from matching and direct magnitude estimation task are similar, but both differ from the rating scale task, suggesting that the matching task provides perceptual distances with ratio-level measurement properties. CONCLUSIONS: The matching task is advantageous for measurement of vocal quality because it provides reliable measurement with ratio-level scale properties. It allows the use of a fixed reference signal for all comparisons, thus allowing researchers to directly compare findings across different experiments.